Equine meniscal degeneration is associated with medial femorotibial osteoarthritis - Dubuc, J.; Girard, C.; Richard, H.; De Lasalle, J.; Laverty, S. (Wiley, 2018)
Background: There is limited information available concerning normal equine meniscal morphology, its degeneration and role in osteoarthritis (OA). Objectives: To characterise normal equine meniscal morphology and lesions and to explore the relationship between equine meniscal degeneration and femorotibial OA. Study design: Ex vivo cadaveric study. Methods: Menisci were harvested from 7 normal joints (n = 14 menisci) and 15 joints with OA (n = 30 menisci). A macroscopic femorotibial OA score (cartilage degeneration and osteophytosis) was employed to measure disease severity in each compartment. The femoral and tibial meniscal surfaces were scored for macroscopic fibrillation and tears (1–4). Histological sections (regions: cranial and caudal horn; body) were also scored for microscopic fibrillation and tears (0–3) and inner border degeneration (0–3). Results: Partial meniscal tears were present on both femoral and tibial surfaces in all 3 regions and most frequently identified on the femoral surface of the cranial horn of the medial meniscus and body of the lateral meniscus. There was a significantly positive correlation between the global medial meniscal macroscopic scores and osteophyte (r = 0.7, P = 0.002) or cartilage degeneration (r = 0.5, P = 0.03) scores within the medial femorotibial joint. The global medial meniscal macroscopic score was greater (P = 0.004) in the advanced OA joints compared with control joints. Main limitations: The menisci were principally from abattoir specimens without a known clinical history because of the challenge in obtaining a large number of specimens with a clinical diagnosis of femorotibial OA. Conclusions: This study is the first to describe normal equine meniscal morphology and lesions. Meniscal lesions were identified in all segments and on both articular surfaces. Meniscal degeneration significantly correlated with OA severity in the equine medial femorotibial joint. The relationship between OA and meniscal pathology remains to be elucidated.